2014
DOI: 10.1016/j.ejvs.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

CTA with Fluoroscopy Image Fusion Guidance in Endovascular Complex Aortic Aneurysm Repair

Abstract: Image fusion guidance provides added value in complex endovascular interventions. The technology significantly reduces iodinated contrast material dose and procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…Similar results were reported by another group who evaluated fenestrated and branched endografts [13]. Iodinated contrast material volume and procedural time were significantly lower in the fusion group than in case controls (159 versus 199 mL and 5.2 versus 6.3 h, respectively).…”
Section: Clinical Applications and Review Of The Literaturesupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were reported by another group who evaluated fenestrated and branched endografts [13]. Iodinated contrast material volume and procedural time were significantly lower in the fusion group than in case controls (159 versus 199 mL and 5.2 versus 6.3 h, respectively).…”
Section: Clinical Applications and Review Of The Literaturesupporting
confidence: 87%
“…Potential pitfalls are inappropriate matching of CT volume and fluoroscopy, leading to misregistration. Respiration-related and cardiac cycle-related vessel displacement, vessel elongation, and displacement by stiff devices and patient movement have been identified as reasons for fusion image inaccuracy [13]. The insertion of rigid (stent) delivery systems into the vascular system can significantly alter the anatomical relations due to "stretching out" of the vessels.…”
Section: Clinical Applications and Review Of The Literaturementioning
confidence: 99%
“…The relationship with extension of the aneurysm has been reported previously, and is most likely related to the coverage of the aorta and corresponding spinal cord blood supply. 7 However, the effects of the contrast volume seem to reflect something beyond the technical experience and adjunctive imaging techniques as this was statistically significant between the two time periods, as opposed to SCI incidence which did not reach significance. 14,15 Furthermore, experimental studies have suggested the possibility for these collateral networks to compensate for the hemodynamic changes within 5 days of segmental occlusion.…”
Section: Discussionmentioning
confidence: 89%
“…7 Arterial access was obtained from the right axillary artery and both femoral arteries. Iodine contrast was routinely used, except for SMA and celiac trunk visualization where CO 2 was used.…”
Section: Introductionmentioning
confidence: 99%
“…Optionally, one can consider using 3D CT image fusion to reduce the number of DSA runs, especially in complex fenestrated and branched EVAR. 22,23 …”
Section: Discussionmentioning
confidence: 99%